The Morphosyntactic Properties of English Textspeak in Social Media and Digital Communication - Nadia A-Shawafi (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This study investigates the morphosyntactic properties of English Textspeak which is a highly informal and abbreviated register of English written communication used in social media and online digital communication. The study employs a descriptive analytical approach, utilizing data collected by the researcher from social media and online digital communication platforms and posts. The study finds that English Textspeak demonstrates the rule-governed creativity and flexibility of human language. It shows that Textspeak's words, exemplified by 'lol', 'asap', 'omg', etc. demonstrate key morphosyntactic properties of English individual lexical items, including lexical integrity, lexicalization, lexical category, 'inflectionality', 'referentiality' and 'mobility'. The study reveals that Textspeak primarily modifies and shortens established English words and phrases through productive and systematic morphological processes to adapt to the brevity needs, speed up typing, fast-paced text messaging and efficiency requirements of new technologies. Furthermore, Textspeak's sentences maintain the core-linguistic system, preserving the fixed word order (SVO), hierarchical structure and phonological features of Standard English. The analysis of the data collected also uncovers that the key syntactic properties of Textspeak include the extensive use of ellipsis, and punctuation and capitalization variations to convey tone, emotion, intended meaning and emphasis. The study concludes that Textspeak is not a degradation or deterioration of Standard English. It applies the morphological and syntactic rules of Standard English in a productive and creative way to cope with the requirements of new technologies. The extensive use of shortening processes and ellipsis highlights its systematic optimization for brevity, speed and fast-spaced social media and online digital communication. This study constitutes a foundational contribution to the discipline of morphosyntactic studies, providing significant insights that enhance scholarly understanding.